2014
DOI: 10.3390/toxins6123426
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Control in Maize by Trametes versicolor

Abstract: Aspergillus flavus is a well-known ubiquitous fungus able to contaminate both in pre- and postharvest period different feed and food commodities. During their growth, these fungi can synthesise aflatoxins, secondary metabolites highly hazardous for animal and human health. The requirement of products with low impact on the environment and on human health, able to control aflatoxin production, has increased. In this work the effect of the basidiomycete Trametes versicolor on the aflatoxin production by A. flavu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…Although aflatoxin degradation by fungal laccase enzymes has already been reported [ 15 , 25 , 26 ], to date no direct and unambiguous correlation between laccase and aflatoxin degradation has been described, since cultured filtrates or LC commercial preparation were tested in the degradation assays.…”
Section: Discussionmentioning
confidence: 99%
“…Although aflatoxin degradation by fungal laccase enzymes has already been reported [ 15 , 25 , 26 ], to date no direct and unambiguous correlation between laccase and aflatoxin degradation has been described, since cultured filtrates or LC commercial preparation were tested in the degradation assays.…”
Section: Discussionmentioning
confidence: 99%
“…The use of laccases may result in rapid and significant recalcitrant substrate degradation (Ruiz‐Duenas & Martinez, 2009). Laccases have potential in the degradation of the aflatoxin which, was suggested by the different literatures (Alberts, Gelderblom, Botha, & van Zyl, 2009; Dellafiora, Galaverna, Reverberi, & Dall'Asta, 2017; Loi et al., 2016; Scarpari et al., 2014)…”
Section: Introductionmentioning
confidence: 91%
“…Some notable exceptions were found during studies of enzymatic detoxification: peroxidases and laccases can also modify the substrate and may destroy valuable food components. It is reported that the laccase from Trametes versicolor is able to degrade AFB 1 . The potential for mycotoxin detoxification by enzymatic activities has been recently reviewed …”
Section: Detoxification/inactivation Of Mycotoxinsmentioning
confidence: 99%